Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the value of \(y\) that satisfies the equation \( y = \frac{2}{3} x - 4 \) when \( x = 9 \), follow these steps:
1. Substitute \( x = 9 \) into the equation \( y = \frac{2}{3} x - 4 \).
[tex]\[ y = \frac{2}{3} (9) - 4 \][/tex]
2. Multiply \( \frac{2}{3} \) by 9.
[tex]\[ \frac{2}{3} \times 9 = 6 \][/tex]
3. Subtract 4 from the result obtained in the previous step.
[tex]\[ 6 - 4 = 2 \][/tex]
Thus, the value of \( y \) that makes the equation \( y = \frac{2}{3} x - 4 \) true when \( x = 9 \) is \( y = 2 \).
Therefore, the correct answer is:
A) 2
1. Substitute \( x = 9 \) into the equation \( y = \frac{2}{3} x - 4 \).
[tex]\[ y = \frac{2}{3} (9) - 4 \][/tex]
2. Multiply \( \frac{2}{3} \) by 9.
[tex]\[ \frac{2}{3} \times 9 = 6 \][/tex]
3. Subtract 4 from the result obtained in the previous step.
[tex]\[ 6 - 4 = 2 \][/tex]
Thus, the value of \( y \) that makes the equation \( y = \frac{2}{3} x - 4 \) true when \( x = 9 \) is \( y = 2 \).
Therefore, the correct answer is:
A) 2
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.